Nanofluid flow and heat transfer of carbon nanotube and graphene platelette nanofluids in entrance region of microchannels - Fuller, M.E.; Liu, J.T.C. (Archives of Mechanics, 2020)
Suspensions of nano-scale particles in liquids, dubbed nanofluids, are of great interest for heat transfer applications. Nanofluids potentially offer superior thermal conductivity to alternative, pure fluids and are of particular interest in applications where active cooling of power-dense systems is required. In this work, the thermophysical properties of carbon nanotube nanofluids (CNTNf) and those of graphene nanoplatelette nanofluids (GNPNf) as functions of particle volume fraction are deduced from published experiments. These properties are applied to a perturbative boundary layer model to examine how the velocity and temperature profiles (and correspondingly shear stress and surface heat transfer) vary with the nanoparticle concentration in the entrance region of microchannels. Findings of this modeling effort indicate that both shear stress and heat transfer in GNPNf increase with increasing particle concentration. The normalized increase in shear stress is approximately twice that for heat transfer as a function of the GNP particle concentration. Interestingly, CNTNf shows anti-enhancement heat transfer behaviour; an increasing concentration of CNT nanoparticles is associated with both an increase in shear stress and a decrease in the surface heat transfer rate.